2004
DOI: 10.1161/01.hyp.0000124670.03674.15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms Responsible for Postmenopausal Hypertension

Abstract: Abstract-Blood pressure increases in many women after menopause. Hypertension is one of the major risk factors for cardiovascular disease. However, the mechanisms responsible for the postmenopausal increase in blood pressure are yet to be elucidated. Various humoral systems have been proposed to play a role in postmenopausal hypertension, such as changes in estrogen/androgen ratios, increases in endothelin and oxidative stress, and activation of the renin-angiotensin system (RAS). In addition, obesity, type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
2
17

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(186 citation statements)
references
References 71 publications
8
159
2
17
Order By: Relevance
“…It has been suggested that this is the result of the relative protection of the women by oestrogen and/or exacerbation in the men by androgen 27 although hormone replacement therapy has not been shown to consistently lower BP in postmenopausal women. 28 Our study, however, does not fully support this hypothesis because, if correct, it would apply across ethnic groups. The minimal sex difference in BP in Bangladeshi men and women, and the small difference in BP in the Pakistani and other South Asian groups, requires an explanation other than the 'sex hormone' theory.…”
Section: Discussion Of the Key Findingscontrasting
confidence: 66%
“…It has been suggested that this is the result of the relative protection of the women by oestrogen and/or exacerbation in the men by androgen 27 although hormone replacement therapy has not been shown to consistently lower BP in postmenopausal women. 28 Our study, however, does not fully support this hypothesis because, if correct, it would apply across ethnic groups. The minimal sex difference in BP in Bangladeshi men and women, and the small difference in BP in the Pakistani and other South Asian groups, requires an explanation other than the 'sex hormone' theory.…”
Section: Discussion Of the Key Findingscontrasting
confidence: 66%
“…In general, postmenopausal women tend toward obesity more than premenopausal women, and their blood pressure levels and visceral fat levels are known to increase (34,35). A study taking this into account is needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The transition from pre-to post-menopause may be associated with features of the metabolic syndrome, including an increased central body fat, a shift toward a more atherogenic lipid profile, and high blood pressure. 12,[28][29][30] The emergence of these CVD risk factors may be a direct result of ovarian failure, or an indirect result of the metabolic consequences of body fat centralization with estrogen deficiency. Previous studies have also demonstrated that menopause is associated with a modest increase in total fatness and an accelerated accumulation of central body fat that exceeds changes normally attributed to the aging process.…”
Section: Discussionmentioning
confidence: 99%